PERANCANGAN BUKU CERITA BERGAMBAR SEBAGAI MOTIVASI DIRI BAGI SISWA SMP - Richa Agnellia Utarie, Drs. M. Nasrul Kamal, M.Sn. Riri Trinanda, S.Pd., M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2018)
Exam time that solid can make JHS students is stress. Then an effective educational media is needed to refresh the students brain performance. Educational media that will be used is a book specially designed to motivate learning, this book aims to help restore the mood or spirit of students who are tired in the lesson. The methodology used is 5W + 1H approach which is used as the basic concept of problem solving. This book is assisted by other media such as sticker, bookmark, poster, Pin, Notebook, Clock, T-shirt, Instagram.Key search : Book, Story Illustration, Motivation, Study Motivatian, National Exam.